Krisis Kepercayaan Publik: Kritis Terhadap Pengesahan Undang-undang Perampasan Aset Pada Akun @dpr_ri - Namira Azzahra Putriaji; Roma Kyo Kae Saniro; Anggun Putri Herlina; Hasyif Raqi Al Fadhen; Nanda Gita Aurellia; Rori Islami Sandika; Wulan Sari; Danial Julianda; Nayaka Artalya Marela (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This study aims to analyze lexical meaning, situational meaning, and the intended purpose conveyed in comments related to the issue of the "Ratification of the Asset Seizure Law" on the official Instagram account of the Indonesian House of Representatives (@dpr_ri). The high public response on social media, especially on the @dpr_ri Instagram account, shows that Instagram serves as a platform for people to express criticism, opinions, and aspirations. This study uses a descriptive qualitative method with data sourced from 25 netizen comments on @dpr_ri posts, dominated by non-standard sentences, emotional expressions, and sarcasm regarding the slow process of ratifying the Asset Seizure Bill. This study contributes to the public understanding of proper language use on social media as well as the importance of language literacy in expressing criticism ethically and effectively.